The Effect Of Stress Management On Work Productivity In The Company Environment - Ida Ayu Trisna Wijayanthi; Tettie Setiyarti; Ida Ayu Komang Juniasih; Ida Bagus Radendra Suastama; Ni Ketut Laswitarni (Maneggio, 2024)
This study focuses on the problem of stress management and its influence on employee work productivity in a culinary company in Denpasar. High stress can affect employee performance, so it is necessary to make efforts to manage stress effectively. The purpose of this study is to analyze the relationship between stress management and employee work productivity. The method used is a quantitative approach with a questionnaire distributed to 127 respondents who are employees in various culinary companies. The data obtained were analyzed using simple linear regression to test the influence of stress management variables on productivity. This study uses the SPSS Version 25 analysis tool. The results showed that there was a positive and significant influence between stress management and employee work productivity, with the R Square value showing the proportion of productivity variation that can be explained by stress management. The conclusion of this study is that improved stress management can increase work productivity, so it is important for companies to implement effective stress management strategies. The implications of this study suggest that companies develop stress management programs, such as skills training and increased social support in the workplace, in order to create a healthier and more productive work environment. Thus, this study contributes to the understanding of the importance of stress management in the context of improving employee performance in the culinary industry, and can be a reference for further research in this field.